Serum Albumin Is Independently Associated with Persistent Organ Failure in Acute Pancreatitis - Wandong Hong; Suhan Lin; Maddalena Zippi; Wujun Geng; Simon Stock; Zarrin Basharat; Bicheng Cheng; Jingye Pan; Mengtao Zhou (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. To investigate the association between serum albumin levels within 24 hrs of patient admission and the development of persistent organ failure in acute pancreatitis. Methods. A total of 700 patients with acute pancreatitis were enrolled. Multivariate logistic regression and subgroup analysis determined whether decreased albumin was independently associated with persistent organ failure and mortality. The diagnostic performance of serum albumin was evaluated by the area under Receiver Operating Characteristic (ROC) curves. Results. As levels of serum albumin decrease, the risk of persistent organ failure significantly increases (Ptrend<0.001). The incidence of organ failure was 3.5%, 10.6%, and 41.6% in patients with normal albumin and mild and severe hypoalbuminaemia, respectively. Decreased albumin levels were also proportionally associated with prolonged hospital stay (Ptrend<0.001) and the risk of death (Ptrend<0.001). Multivariate analysis suggested that biliary etiology, chronic concomitant diseases, hematocrit, blood urea nitrogen, and the serum albumin level were independently associated with persistent organ failure. Blood urea nitrogen and the serum albumin level were also independently associated with mortality. The area under ROC curves of albumin for predicting organ failure and mortality were 0.78 and 0.87, respectively. Conclusion. A low serum albumin is independently associated with an increased risk of developing of persistent organ failure and death in acute pancreatitis. It may also be useful for the prediction of the severity of acute pancreatitis.